Contrarian and momentum in Chinese stock markets. - Ni, Xiaoyan. (2008)
This thesis has investigated the stock return patterns in Chinese stock markets by testing whether momentum or contrarian exists in short and intermediate time horizon. Using sample stocks from Shanghai Stock Exchange and Shenzhen Stock Exchange we find that both short-term contrarian and intermediate-term momentum profits can be observed.